Varietal Differences in Properties Among High Amylose Rice Starches - Juliano, Bienvenido O.; Villareal, R.M.; Perez, C.M.; Villareal, C.P.; Baños, Los; Takeda, V.; Hizukuri, S. (Wiley, 1987)
Among three high‐amylose starches differing in gel consistency, the hard gel starch (IR42), corresponding to harder cooked rice, had higher amylograph consistency and setback, higher gel viscosity in 0.2 N KOH and higher alkali viscograph peak than starch with soft (IR32) or medium (IR36) gel consistency. IR42 starch had less extractable starch and amylose in boiling water than IR32 and IR36 starches. The three starches had similar amyloses; the differences in gel consistency were due to the amylopectin fraction. IR42 amylopectin had higher iodine affinity, more long‐chain linear fractions on isoamylase debranching and gel filtration or 1‐butanol precipitation, and less DPn 16–17 fraction than IR32 and IR36 amylopectins.